2021
DOI: 10.1093/mnras/stab225
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the imposed magnetospheres of Mars-like exoplanets: star–planet interactions and atmospheric losses

Abstract: Based on 3D compressible magnetohydrodynamic (MHD) simulations, we explore the interactions between the magnetized wind from a solar-like star and a Mars-like planet – with a gravitionally stratified atmosphere – which is either non-magnetized or hosts a weak intrinsic dipolar field. The primary mechanism for the induction of a magnetosphere around a non-magnetized conducting planet is the pile-up of stellar magnetic fields in the day side region. The magnetopause stand-off distance decreases as the strength o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 64 publications
1
15
0
Order By: Relevance
“…When we perform the simulation with a non-magnetized planet, we find an induced magnetosphere around the nonmagnetized planet (see Figure 5). This reaffirms previous findings (Stevenson 2003;Ma et al 2013;Basak & Nandy 2021) that non-magnetized planet possess an induced magnetosphere. Figure 5 shows the density modulations of the surrounding medium due to the induced magnetosphere when the planet is non-magnetized.…”
Section: Short-orbit Casesupporting
confidence: 92%
See 2 more Smart Citations
“…When we perform the simulation with a non-magnetized planet, we find an induced magnetosphere around the nonmagnetized planet (see Figure 5). This reaffirms previous findings (Stevenson 2003;Ma et al 2013;Basak & Nandy 2021) that non-magnetized planet possess an induced magnetosphere. Figure 5 shows the density modulations of the surrounding medium due to the induced magnetosphere when the planet is non-magnetized.…”
Section: Short-orbit Casesupporting
confidence: 92%
“…In our solar system, interaction between the solar wind and the Venus atmosphere is an ideal example of such an unipolar interaction. It was shown that the unipolar interaction leads to the creation of an induced magnetosphere having similar global structure like other self-generated planetary magnetosphere (e.g., Luhmann et al 1981;Kivelson & Russell 1995;Russell et al 2006;Basak & Nandy 2021). However, (e.g., Ma et al 2013) have shown that induced magnetosphere has much less spatially extended compared to the self-generated planetary magnetoshpere.…”
Section: Short-orbit Casementioning
confidence: 99%
See 1 more Smart Citation
“…The global magnetic field distribution in the Sun and stars, its parity, and the structure of coronal magnetic fields are governed by the dynamo mechanism (Dash et al, 2023) and surface emergence and evolution of magnetic flux (Nandy et al, 2018;Kavanagh et al, 2021). The magnetic field topology in turn determines the global stellar magnetosphere and magnetized stellar wind (Réville et al, 2015;Vidotto et al, 2014b) that play critical roles in star-planet interactions (Das et al, 2019;Basak and Nandy, 2021;Carolan et al, 2021) and the forcing of (exo)planetary space environments (Nandy et al, 2021;Hazra et al, 2022). Also, the stellar magnetic cycle alters the total X-ray and EUV (XUV) radiation from host stars affecting exoplanetary atmospheres (Hazra et al, 2020).…”
Section: Extrapolation To Stellar Dynamosmentioning
confidence: 99%
“…Gravitational (tidal) interactions can be neglected if the planet lies far away (as in the case for Sun-Earth system) and in such a scenario, the stellar wind independently affects the planetary environment without the possibility of the coronal structure of the star getting modified. The evolution of planetary atmospheres and the nature of its interaction with the stellar wind are profoundly affected by changes in their respective magnetic field strengths (Cohen et al 2015;Basak & Nandy 2021). Discovery of several exoplanets (Mayor & Queloz 1995;Pepe et al 2014;Lunine et al 2009) has sparked interest in exploring the signatures of life-sustaining conditions and understanding habitability from the perspective of the origin and evolution of planetary atmospheres (Lammer et al 2009;Lammer 2013;Pollack & Yung 1980;Cridland et al 2017).…”
Section: Introductionmentioning
confidence: 99%